A novel Pectobacterium brasiliense-infecting phage from Egypt with biocontrol potential against soft rot in vegetables - Elhalag, Kamel M.; Ahmad, Abdelmonim Ali; Elsharkawy, Mohsen Mohamed; Huang, Qi; Nasr-Eldin, Mohamed A. (Frontiers in Microbiology, 2025)
Pectobacterium brasiliense causes soft rot in many economically important crops, including vegetables and ornamentals, leading to significant yield losses. Traditional antibiotics, bactericides, and antimicrobial agents face limitations such as bioaccumulation on plants and the emergence of microbial resistance. Bacteriophages (phages) offer a promising alternative for effective control of a variety of phytopathogens. In this study, we isolated and characterized a virulent phage as a potential biocontrol agent against P. brasiliense. The phage was designated as PbrM1EGY, as it specifically targets only tested strains of P. brasiliense (Pbr) and is the first Myoviridae phage (M1) isolated from Egypt (EGY). The phage has an icosahedral head measuring 46.3 ± 3.9 nm and a long, contractile tail of 99.9 ± 3.9 nm. Phage PbrM1EGY exhibited relative stability across a wide range of environmental conditions, including pH (3 to 11), temperatures (4–50°C), NaCl concentrations (1–15%), and ultraviolet light exposure (1–15 min). It takes about 50 min for PbrM1EGY to complete its lytic cycle with a latent period of approximately 20 min and an average burst size of 749 ± 40 PFU per infected cell. At MOIs of 0.01, 0.1 and 1, phage PbrM1EGY significantly reduced the in vitro growth of P. brasiliense compared to the bacterial control without phage treatment. When tested in planta, the phage effectively prevented the development of soft rot symptoms in pepper and cucumber fruits, carrot roots, and potato tubers, while significantly reducing tissue maceration in onion bulbs. Our findings suggest that phage PbrM1EGY has great potential as a biocontrol agent against soft rot disease caused by P. brasiliense in vegetable crops, including pepper, cucumber, carrot, onion and potato.